Water management practices and aedes aegypti pupal density among households in selected barangays in Muntinlupa City - Mationg, Mary Lorraine S.
Aedes aegypti is the primary vector of dengue, the most serious arboviral infection globally. Until an effective vaccine is approved and rigorously administered, Aedes aegypti control remains to be the cornerstone in preventing and curtailing dengue transmission. Using secondary data from a previous cross-sectional study that looked into the eco-bio-social determinants of dengue vector breeding among households in barangays of Muntinlupa City, an analytical study design was used for this particular study to evaluate the association between water management practices and Aedes Aegypti pupal density. Water management includes practices like covering of water-holding containers and using-up stored water within one week. Aedes Aegypti pupal density was determined at the household level. Multiple Logistic Regression (MLR) was used in the analysis to determine the association between the variables representing water management practices and density of the vector. Results showed that adequate covering of containers is significantly associated with Aedes Aegypti pupal density. Households with inadequately covered essential water-holding containers were 2.32 times (95% CI: 1.07-5.01) more likely with high Aedes Aegypti pupal density compared to households with adequately covered essential water-holding containers. Using-up stored water within a week in 100% of the essential water-holding containers was also associated with high Aedes aegypti pupal density. Households that failed to use the stored water in essential water-holding containers within a week were 2.29 time (95% CI: 1.05-4.99) more likely with high Aedes aegypti pupal density compared to households that used the stored water in essential water-holding containers within a week. Water management practices, specifically, inadequate covering of essential water-holding containers and prolonged storage of water (beyond one week) were associated with the Aedes aegypti pupal density in the hoouseholds. Among the variables examined for potential effect measure modification (I.e.. knowledge on dengue, type of water source and the presence of non essential water-holding containers), none was found to be statistically significant.